SENSORY AND NUTRITIONAL QUALITY OF SWEET RECIPES PREPARED USING DATES PALM JAGGERY - Nande, Dr. Prajakta Jayant (IJRDO-Journal of Applied Science, 2016)
Present study deals with preparation of experimental recipes like diamond cuts, sweetrice, sesame seeds laddoo & pumpkin kheer using dates palm jaggery. Control recipeswere prepared using sugarcane jaggery. Sensory evaluation was carried out in threetrials by six judges. Diamond cuts made using dates palm jaggery were highlyaccepted for all sensory attributes (perfect scores of 10). Appearance, colour,doneness & texture of experimental sweet rice & sesame seeds laddoo prepared usingdates palm jaggery received identical mean scores (10 for very good) to that of controlsweet rice & sesame seeds laddoo prepared using sugarcane jaggery. Experimentalpumpkin kheer prepared with dates palm jaggery was significantly rated abovecontrol pumpkin kheer prepared with sugarcane jaggery for appearance & colour(t=5.88, p<0.01). All experimental recipes were found energy dense, good incarbohydrate, protein & fat.